Pelatihan Pembuatan Lotion Antinyamuk Berbasis Minyak Atsiri untuk Meningkatkan Pengetahuan Siswa SMAN 30 Garut - Aika Latifah Alawiyah; Fajar Fauzi Abdullah; Ruchiyat; Farid Perdana; Isye Martiani; Jasminum Sambact; Rahma Mekar Muharram (Institut Pertanian Bogor, 2026)
Mosquitoes are considered vectors responsible for dengue fever, malaria, and chikungunya. Applying anti-mosquito lotion is a precaution to avoid mosquito bites. Certain commercial items contain diethyltoluamide (DEET), which can be harmful to health and contaminate the environment when used for extended periods. Utilizing essential oils in a anti-mosquito lotion is more eco-friendly. This community service aimed to improve students’ understanding and ability to produce anti-mosquito lotion using essential oils. The training took place at SMAN 30 Garut, involving 35 students from classes X and XII. The training approach involves preparation; implementation (pre-test and post-test to evaluate participants’ knowledge levels, delivering material interactively, and practicing); and evaluating activities through satisfaction questionnaires. A paired t-test analysis of the pre-test and post-test results showed that a t-value of 3,25 with a p-value of 0,012 (< 0,05), indicating a significant improvement in the pupils’ knowledge of the subject matter and their skills in making mosquito-repellent lotion. The percentage of correct answers has increased from 68,57% (pre-test) to 86,35% (post-test). The results indicated that participants responded positively to the activities conducted. The results of the training showed an improvement in students’ understanding of the subjectand their ability to make anti-mosquito lotions. This activity not only provides insight into the use of natural products but also raises students’ interest in entrepreneurial oppoturnities and innovation within schools and the community.